Endothelial Expression of Scavenger Receptor Class B, Type I Protects against Development of Atherosclerosis in Mice. (4th October 2015) - Vaisman, Boris L.; Vishnyakova, Tatyana G.; Freeman, Lita A.; Amar, Marcelo J.; Demosky, Stephen J.; Liu, Chengyu; Stonik, John A.; Sampson, Maureen L.; Pryor, Milton; Bocharov, Alexander V.; Eggerman, Thomas L.; Patterson, Amy P.; et al.
Abstract : The role of scavenger receptor class B, type I (SR-BI) in endothelial cells (EC) was examined in several novel transgenic mouse models expressing SR-BI in endothelium of mice with normal C57Bl6/N, apoE-KO, or Scarb1 -KO backgrounds. Mice were also created expressing SR-BI exclusively in endothelium and liver. Endothelial expression of the Tie2- Scarb1 transgene had no significant effect on plasma lipoprotein levels in mice on a normal chow diet but on an atherogenic diet, significantly decreased plasma cholesterol levels, increased plasma HDL cholesterol (HDL-C) levels, and protected mice against atherosclerosis. In 8-month-old apoE-KO mice fed a normal chow diet, the Tie2- Scarb1 transgene decreased aortic lesions by 24%. Mice expressing SR-BI only in EC and liver had a 1.5 ± 0.1-fold increase in plasma cholesterol compared to mice synthesizing SR-BI only in liver. This elevation was due mostly to increased HDL-C. In EC culture studies, SR-BI was found to be present in both basolateral and apical membranes but greater cellular uptake of cholesterol from HDL was found in the basolateral compartment. In summary, enhanced expression of SR-BI in EC resulted in a less atherogenic lipoprotein profile and decreased atherosclerosis, suggesting a possible role for endothelial SR-BI in the flux of cholesterol across EC.